Reviews of new publications - Lambert, Frank (KUKILA, 2012)
Handbook of the Birds of the World. Volume 16: 2011. Tanagers to New World Blackbirds. del Hoyo, J., Elliot, A. and Christie, D.A. (eds). Lynx Edicions, Barcelona. ISBN-978-84-96553-78-1. 893 pages, including 81 colour plates, 499 photos and 766 distribution maps.